2009
DOI: 10.1029/2008jb005866
|View full text |Cite
|
Sign up to set email alerts
|

Clay fabric intensity in natural and artificial fault gouges: Implications for brittle fault zone processes and sedimentary basin clay fabric evolution

Abstract: [1] The role of phyllosilicate fabrics in fault gouge is a poorly understood component of the mechanical and hydrologic behavior of brittle fault zones. We present 90 fabric intensity measurements using X-ray texture goniometry on 22 natural clay-rich fault gouges from low-angle detachment faults (Death Valley area detachments, California; Ruby Mountains, Nevada; West Salton Detachment Fault, California) and the Peramola thrust in NE Spain. Natural fault gouges have uniformly weak clay fabrics (multiples of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 130 publications
(187 reference statements)
8
71
0
Order By: Relevance
“…4-7). It shows a distinctive, well organized P foliation (orientation nomenclature sensu Logan et al, 1979) with a high fabric intensity (sensu Yan, 2001;Haines et al, 2009). Correspondingly, ultrathin sections of gouge display a uniform extinction pattern along the P foliation under crossed polars (not shown here; refer to Laurich et al, 2014).…”
Section: Microstructurementioning
confidence: 99%
“…4-7). It shows a distinctive, well organized P foliation (orientation nomenclature sensu Logan et al, 1979) with a high fabric intensity (sensu Yan, 2001;Haines et al, 2009). Correspondingly, ultrathin sections of gouge display a uniform extinction pattern along the P foliation under crossed polars (not shown here; refer to Laurich et al, 2014).…”
Section: Microstructurementioning
confidence: 99%
“…Predictions of mechanical and transport properties over long timescales are essential for the evaluation of subsurface integrity. For this, it is generally agreed that a multiscale experimental approach that combines measurement of bulk mechanical and transport properties with microstructural study to identify deformation mechanisms is required to develop microphysics-based constitutive equations, which can be extrapolated to timescales not available in the laboratory, after comparison with naturally deformed specimens (Morgenstern and Tchalenko, 1967;Tchalenko, 1968;Lupini et al, 1981;Rutter et al, 1986;Logan et al, 1979Logan et al, , 1987Logan et al, , 1992Marone and Scholz, 1989;Evans and Wong, 1992;Katz and Reches, 2004;Niemeijer and Spiers, 2006;Colletini et al, 2009;Haines et al, 2009Haines et al, , 2013French et al, 2015;Crider, 2015;Ishi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies of fabric formation in fine-grained sediments have shown that mechanical rotation of pre-existing grains is only capable of producing fabrics up to about 10 m.r.d. (Tullis, 1976;Haines et al, 2009). Hence, the extremely strong muscovite and chloritoid texture in the sample of the MASB has to result from a preferred metamorphic mineral growth in response to a differential stress (cf.…”
Section: Discussionmentioning
confidence: 99%